Time Difference Correction and Location Method for USB Asynchronous Microphone Arrays. Issue 1 (1st November 2022) - Wang, Zhisheng; Yu, Hanze; Cui, Junning
Abstract: To address the problem of asynchronous delay caused by combining at least two array platforms in 2D/3D location, in this paper, we analyze the impact of time difference between asynchronous devices on time-delay estimation from the experimental phenomenon. Then, we propose a USB asynchronous correction algorithm which takes the known propagation delay as the benchmark, the time difference of asynchronous equipment is calculated by offseting the time delays on the left and right sides. The experimental results show it can correct the time difference for USB asynchronous microphone arrays, which achieve a great location accuracy.